Renormalized solutions for the fractional p(x)-Laplacian equation with L1 data. (January 2020) - Zhang, Chao; Zhang, Xia
Abstract: We consider the fractional p ( x ) -Laplacian problem with L 1 data. Based on the approximation and energy methods, we prove the existence and uniqueness of nonnegative renormalized solutions for such problems.